2017
DOI: 10.1016/j.apsb.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

T cell--associated immunoregulation and antiviral effect of oxymatrine in hydrodynamic injection HBV mouse model

Abstract: Although oxymatrine (OMT) has been shown to directly inhibit the replication of hepatitis B virus (HBV) in vitro, limited research has been done with this drug in vivo. In the present study, the antiviral effect of OMT was investigated in an immunocompetent mouse model of chronic HBV infection. The infection was achieved by tail vein injection of a large volume of DNA solution. OMT (2.2, 6.7 and 20 mg/kg) was administered by daily intraperitoneal injection for 6 weeks. The efficacy of OMT was evaluated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The intracellular expression of cytokines in T-cells was analyzed using an eBioscience intracellular staining kit as previous reported 28 . Briefly, spleen cells from mice were incubated with PMA (100 ng/mL)/ionomycin (1 μg/mL) and monesine (1 μg/mL) in complete media at 37 °C for 6 h. The cells were first surface stained with CD4-FITC or CD8-APC for 15 min at 4 °C, then fixed and permeabilized with fixation and permeabilization wash buffers respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The intracellular expression of cytokines in T-cells was analyzed using an eBioscience intracellular staining kit as previous reported 28 . Briefly, spleen cells from mice were incubated with PMA (100 ng/mL)/ionomycin (1 μg/mL) and monesine (1 μg/mL) in complete media at 37 °C for 6 h. The cells were first surface stained with CD4-FITC or CD8-APC for 15 min at 4 °C, then fixed and permeabilized with fixation and permeabilization wash buffers respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, extensive researches have reported that OMT have anticancer effects by inducing cell cycle arrest, apoptosis and inhibition of angiogenesis in various cancer cells in vitro and in vivo (24). In the previous studies, immunoregulatory effects of OMT on hepatitis B of mice, rheumatoid arthritis in rats and mastitis in mice have been confirmed (2527). Considering the extensive effects of OMT, we investigate the effect of OMT in combination with DDP on anti-tumor immunity in NSCLC and elucidate the potential mechanism.…”
Section: Introductionmentioning
confidence: 78%
“…Our results also showed that in HBV-replicating mouse model, LWWL treatment significantly increased the frequency of CD3 + CD4 + T cells and serum IFN-γ production. IFN-γ is mainly generated by activated CD3 + CD4 + T cells, and IFN-γ has been proved to be able to inhibit HBV replication through triggering intracellular antiviral pathways ( Chokshi et al, 2014 ; Sang et al, 2017 ; Iannacone and Guidotti, 2021 ). We speculated that LWWL might play an anti-HBV role by enhancements of both IFN-β-mediated innate anti-HBV effect and IFN-γ-mediated acquired anti-HBV effect, whereas further studies are needed for the confirmation and elucidation of the context of the pathways.…”
Section: Discussionmentioning
confidence: 99%